Kajian Etnobotani Tumbuhan Obat Tradisional Penyakit Sawan (Solpot) Suku Batak Toba Di Desa Dolok Margu Kecamatan Lintong Nihuta - Annisa Verawaty Siregar; Aswarina Nasution (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
Traditional healing practices are part of cultural heritage that need to be documented as a way to appreciate ancestral heritage. One of these is the use of plants in treating convulsions (solpot). This study aims to determine the beliefs, local knowledge, utilization practices, and secondary metabolites of plants utilized by the Toba Batak people in ethnobotanical-based traditional medicine. This study used a mixed method through observation, interviews with traditional elders, accompanied by analysis of secondary metabolite content in plants used as therapeutic media. The results show that the Toba Batak people believe that plants have the power to cure physical ailments and disorders of supernatural beings. Local knowledge includes nine plant species from eight families with the most common habitus being tree habitus (34%). The plant parts used are predominantly leaves (18%), with the methods of use being drunk and massage (23%). Chemically, medicinal plants for convulsions (solpot) contain secondary metabolites dominated by alkaloids and saponins that play a role in treating seizures and calming nerves.